Hired Men: Ontario Agricultural Wage Labour in Historical Perspective - Parr, Joy (Labour / Le Travail, 1985)
Examines the hierarchy of labour by men on Ontario farms from the colonial period to the 1980s. Argues that despite changes over the past two centuries in in the relationships of labour, capital and land, the rural agricultural class system has endured. Concludes that the farm labour regime of low wages and few legal protections continues to be firmly entrenched.
Keywords: Agriculture; COLONIES; COLONIZATION; Economic activity; Income; Labor; Ontario; RURAL industries; Wages